2018
DOI: 10.1016/j.ecl.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Prediabetes and Cardiovascular Disease

Abstract: Prediabetes is a state characterized by impaired fasting glucose or impaired glucose tolerance. This review discusses the pathophysiology and macrovascular complications of prediabetes. The pathophysiologic defects underlying prediabetes include insulin resistance, alpha- and beta-cell dysfunction, increased lipolysis, inflammation, and suboptimal incretin effect. Recent studies have revealed that the long-term complications of diabetes manifest in some people with prediabetes; these complications include micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
80
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(90 citation statements)
references
References 138 publications
1
80
0
9
Order By: Relevance
“…Prediabetes is a state of intermediate hyperglycaemia that causes abnormal changes in intracellular metabolism of most body tissues including the liver [1]. Presently, the observed increase in the prevalence of prediabetes and type 2 diabetes mellitus (T2DM) in developed and developing countries is reported to be due to sedentary lifestyles coupled with high-caloric diets [1][2][3]. However, studies have shown that excessive intake of high-caloric diets induces skeletal muscle insulin resistance which results into the shunting of glucose from the skeletal muscle to the liver thereby leading to increased hepatic glycogen production and storage [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Prediabetes is a state of intermediate hyperglycaemia that causes abnormal changes in intracellular metabolism of most body tissues including the liver [1]. Presently, the observed increase in the prevalence of prediabetes and type 2 diabetes mellitus (T2DM) in developed and developing countries is reported to be due to sedentary lifestyles coupled with high-caloric diets [1][2][3]. However, studies have shown that excessive intake of high-caloric diets induces skeletal muscle insulin resistance which results into the shunting of glucose from the skeletal muscle to the liver thereby leading to increased hepatic glycogen production and storage [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…2 3 Besides conferring increased risk for T2D, prediabetes is associated with vascular and neuropathic complications. [4][5][6] Several randomized clinical trials have demonstrated the efficacy of lifestyle interventions in delaying the development of T2D in people with prediabetes. [7][8][9][10][11] These landmark studies prespecified diabetes prevention, rather than reversal of prediabetes, as the primary outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated prevalence of Chinese adults with prediabetes was 50.1%, and 493.4 million may have had prediabetes in 2010 [ 2 ]. Prediabetes is an important risk factor for diabetes [ 3 ] and many other diseases, such as cardiovascular diseases (CVD) [ 4 ], stroke [ 5 ], and nephropathy [ 6 ]. It was reported that the annual risk of progressing to diabetes in people with prediabetes was 5%–10% and up to 70% prediabetic patients would develop diabetes after years [ 7 ].…”
Section: Introductionmentioning
confidence: 99%